Investigation on High-Temperature Decomposition and Regeneration Characteristics of Hydroxyapatite Powders and Sinters - Quan, Renfu; Wang, Chunyan; Wang, Hongbin; Wei, Xicheng; Zhao, Zhijun (Asian Journal of Chemistry, 2013)
Hydroxyapapite has been widely used because of its excellent biocompatibility. In this work, we studied the decomposition characteristics of both nano-hydroxyapapite powders prepared by the precipitation method and the corresponding sinters at the temperature from room temperature to 1500 ºC. X-Ray diffractometer, Raman spectroscopy and high temperature differential scanning calorimeter were employed to investigate the decomposition characteristics. Results show that hydroxyapapite powders gradually release the OH– ions from 1000 ºC and decompose into b-tricalcium phosphate (b-TCP) and tetracalcium phosphate (TTCP) when the heating temperature is higher than 1360 ºC and the b-TCP phase changes into a-TCP at about 1450 ºC, which remains if the sinter cools to the room temperature. We also found that the decomposed sinters can reconstitute to hydroxyapapite again under a slow cooling rate and in a certain atmosphere. This work revealed and compared the decomposition and regeneration characteristics of hydroxyapapite powders and sinters, which is useful for the applications of hydroxyapapite materials.